A Comparative Study of Training in the Private and Public Sectors: Evidence from the United Kingdom and the United States - Sepulveda-Pizarro, F (Blackwell Publishing Inc., 2016)
Formal training programs are one of the main channels through which workers become more productive and experience wage growth. So far, however, most of the results on the effects of employer-provided training come from studying the training received by private sector workers only. We extend the literature by identifying and comparing the effects of private-employer-provided and public-employer-provided training in the United States and the United Kingdom. We address this question using two independent data sets from the British Household Panels Surveys and the American National Longitudinal Survey of Youth of 1979. (JEL J24, J31, J40) © 2016 Western Economic Association International.